PENGUJIAN PEMADATAN LUMPUR SAWIT DARI SISA PENGOLAHAN CRUDE PALM OIL (CPO) - Masyita Dewi Koraia (PILAR, 2011)
South Sumatra producing Crude Palm Oil (CPO) in Indonesia. One of  factory is located in the Mariana, Banyuasin - South Sumatra, produces about 1500 tons of palm oil sludge/year. This huge untapped potential. It would be very advantageous if the waste palm oli can be widely used, among other soil stabilization. This research aims to determine the optimum composition of the compaction of sludge palm oil and clay. Compaction testing done to see the optimum water content (woptimum) and dry unit weight maximum (γd max). Variations optimal in mixture are sludge palm oil of 25% and 75% of the clay. The value obtained from the variation of this mixture is the optimum water content (woptimum) = 19.78% and the dry unit weight maximum (γd max) = 1.35 gr/cm3.